2014
DOI: 10.1111/1365-2656.12281
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting spring from afar? Timing of migration and predictability of phenology along different migration routes of an avian herbivore

Abstract: and 8 Vogeltrekstation -Dutch Centre for Avian Migration and Demography (NIOO-KNAW), 6708 PB Wageningen, The Netherlands Summary 1. Herbivorous birds are hypothesized to migrate in spring along a seasonal gradient of plant profitability towards their breeding grounds (green wave hypothesis). For Arctic breeding species in particular, following highly profitable food is important, so that they can replenish resources along the way and arrive in optimal body condition to start breeding early. 2. We compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 36 publications
(52 reference statements)
5
138
0
Order By: Relevance
“…Contrastingly, food peaks are unlikely to advance at temperate sites under warming up to 1.7°C, as out warming treatment did not affect plant growth. The larger warming response of Arctic forage plants which we find can more strongly advance peaks in food availability further along the migratory flyway and thus give rise to mismatches between bird migration and peak food availability (Doiron et al., 2015; Kölzsch et al., 2015; Meltofte et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrastingly, food peaks are unlikely to advance at temperate sites under warming up to 1.7°C, as out warming treatment did not affect plant growth. The larger warming response of Arctic forage plants which we find can more strongly advance peaks in food availability further along the migratory flyway and thus give rise to mismatches between bird migration and peak food availability (Doiron et al., 2015; Kölzsch et al., 2015; Meltofte et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Under a shortening of this period, geese might not have the time to both exploit temperate food peaks prior to migration and still arrive on the breeding grounds on time (Meltofte et al., 2007). Also, as geese time their spring migration according to peaks of nitrogen (van der Graaf et al., 2006), the lack of advancement of food peaks in temperate regions could deteriorate the ability of the geese to predict food conditions on the Arctic breeding grounds (Kölzsch et al., 2015). Either one or the combination of these effects is likely to result in a mismatch between goose migration phenology and peak food availability (Dickey et al., 2008), which has been shown to strongly reduce gosling growth (Doiron et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the timing of the Russian geese migration from the Baltic Sea was not linked to the advancement of plant growth, most likely because of the low correlation in the weather patterns between the Baltic Sea and White Sea (van der Graaf, 2006). Using the third derivative of daily temperature sums (GDDjerk), Kölzsch et al (2015) showed that the geese are able to closely follow the green wave during their spring migration if predictability of climatic conditions was high between stopovers. Therefore, in the case that predictability is low, the geese might rely more on fixed cues such as photoperiod (length of daylight hours), and do not migrate earlier in the year if spring is early.…”
Section: Differences In the Satellite-derived Gwi At Spring Stopover mentioning
confidence: 99%